2008
DOI: 10.1007/s11605-007-0316-7
|View full text |Cite
|
Sign up to set email alerts
|

Complications of PTFE Mesh at the Diaphragmatic Hiatus

Abstract: Paraesophageal hernia repair has been associated with a recurrence rate of up to 42%. Thus, in the last decade, there has been increasing interest in the use of mesh reinforcement of the hiatal repair. Polytetrafluoroethylene (PTFE) is one of the materials that have been used for this purpose, as it is thought to induce minimal tissue reaction. We report two cases in which complications specific to the use of PTFE mesh in this location developed over time. In the first patient, a gastrectomy was required to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 25 publications
(28 reference statements)
1
76
0
9
Order By: Relevance
“…In addition, Gouvas et al reported significantly more cardiac and respiratory symptoms and a delayed esophageal transit time when comparing prosthetic reinforcement to simple crural repair [23]. More importantly, cases of intraluminal esophageal mesh erosion have been reported [6]. On balance, the use of nonabsorbable synthetic mesh should therefore be avoided in proximity to the distal esophagus [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Gouvas et al reported significantly more cardiac and respiratory symptoms and a delayed esophageal transit time when comparing prosthetic reinforcement to simple crural repair [23]. More importantly, cases of intraluminal esophageal mesh erosion have been reported [6]. On balance, the use of nonabsorbable synthetic mesh should therefore be avoided in proximity to the distal esophagus [6].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, cases of intraluminal esophageal mesh erosion have been reported [6]. On balance, the use of nonabsorbable synthetic mesh should therefore be avoided in proximity to the distal esophagus [6]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67,68) Furthermore, the safety of the use of the prosthesis is a matter of concern, because short-and long-term dysphagia as a result of reactive fibrosis around the esophagus, and erosion and fistulization of the foreign material to the viscera have been reported. 8,11,27,69) In order to minimize these adverse effects, a variety of materials have evolved. Different mesh shapes have also been appraised with regard to dysphagia and recurrence rates (Table 2, Fig 1).…”
Section: Crural Repairmentioning
confidence: 99%
“…The use of biological mesh during hiatal hernia repair has been shown to decrease the recurrence rate of hernia lower than that obtained historically without the mesh [8]. The use of synthetic mesh is associated with complications such as oesophageal stricture, erosion, perforation, migration of mesh into oesophagus or stomach, and infections [9][10][11]. This has led to debate regarding the type of mesh material, size, shape, and fixation techniques.…”
Section: Introductionmentioning
confidence: 99%